ABANDONED COFFEE PLANTATIONS: BIODIVERSITY CONSERVATION OR PATH FOR NON-NATIVE SPECIES? CASE STUDY IN A NEOTROPICAL MONTANE FOREST - Zdravko Baruch (Interciencia, 2014)
Abandoned shade coffee plantations are commonplace inNeotropical mountains. Their secondary successional regrowthsupports local biodiversity. However, cultivation terminationexposes the land to introduced colonizing plants, altering vegetationtraits and creating novel communities. We report thevegetation and discuss the possible successional trajectory of acoffee plantation abandoned ~60 years ago on a sloped terrainwithin a montane forest. Four 400m2 plots were surveyed andwoody individuals >1cm in diameter were tallied, soils wereanalyzed and microclimate was recorded. The importance valueindex was calculated for each species, as well as speciesrichness, diversity, equity, stem density, and basal area (BA).Trunk-stem diameter distribution was assessed. Multivariateanalyses related vegetation and environment. Seventy-six species/morphotypes from 28 families were recorded. Plots contrastedin their dominant canopy trees (Syzygium jambos (roseapple),Croton megalodendron (croton) or Ocotea fendleri (laurel)),species richness (23-37 species), Shannon diversity (2.65-3.23), stem density (3450-8150 ha-1) and BA (19.9-50.7m2·ha-1).The main discriminating factor was the predominance of roseapplein one plot aided by active cultivation nearby and by itslife history traits. Succession was greatly influenced by the colonizationpotential and fast growth of rose-apple, establishinga novel forest community type. The answer to the question inthe title will depend of the effective protection against non-nativeinvading species. Currently, considering the level of humanperturbation in Neotropical montane forests, such protectionappears to be hard to achieve.